Penerapan Strategi Konflik Kognitif dalam Pembelajaran Listrik Dinamis - Supliyadi Supliyadi (JP3 (Jurnal Pendidikan dan Profesi Pendidik), 2017)
As a person knowledge increases there will be a higher cognitive balance through assimilation and accommodation. In the assimilation, there will be contact or effective cognitive conflict between the old concept with a new reality. Stimulation of cognitive conflict in learning will greatly assist the process of assimilation that will be more effective and meaningful in students' cognitive structures. This reason is the background to write the thesis entitled â€œApplication of Cognitive Conflict Strategy Learning In Dynamic Electricityâ€. The Application of Cognitive Conflict Strategy in Dynamic Electricity learning is carried out in order to determine whether student achievement is better with the application of cognitive conflict strategy than the conventional learning model. The influence of activity on the achievement of students learning physics concepts through the dynamic power through the implementation strategy of cognitive conflict and to know the structure cognitive students about the concept of dynamic electricity.